Pengaruh Kombinasi Latihan Shadow dan Target Pratice terhadap Akurasi Backhand Drive Tenis Meja Mahasiswa Pendidikan Jasmani Kesehatan & Rekreasi (PJKR) - Muhammad Ishak; Argubi Silwan; Agil Hagaini Hulu; Della Wiyanti; Ingat Berkat Giawa; Khairul Adzmi Faturrahman; Muhammad Reza Nasution; Remika Maretama Situmorang; Win Sara Diwa (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aimed to determine the effect of a combination of shadow and target practice on the accuracy of table tennis backhand drives in Physical Education, Health, and Recreation (PJKR) students. This study used a quantitative approach with a one-group pretest-posttest experimental design. The sample in this study consisted of 20 PJKR students selected using a total sampling technique. The instrument used was a backhand drive accuracy test with a maximum score of 100. The results showed that the average pretest score of 59.35 increased to 75.20 in the posttest, with an average increase of 15.85 points. Based on the results of the hypothesis testing using a paired-sample t-test, the calculated t-value was 121.0, while the t-table value at a significance level of 0.05 with 19 degrees of freedom (df) was 2.093. Because the calculated t-value is greater than the table t-value, the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. These results indicate that the combination of shadow and target practice significantly improves the accuracy of backhand drives in table tennis. Therefore, this training method can be used as an effective alternative for improving basic table tennis technical skills, particularly in PJKR students.